Confronting Forfeiture - Joshua Katz (Washington University Law Review, 2019)
Phil Parhamovich was pulled over on I-80 in Wyoming. He had changed lanes improperly, and his seat belt was not fastened. Seven hundred seventy-five dollars would have been a reasonable fine. Instead, Parhamovich nearly lost 91,800. The money represented his life savings; he was on his way to Wisconsin, where he planned to buy a music studio. During the traffic stop, though, under intensive questioning, he lied. When police suggested that the money was indicative of drug crimes and led Parhamovich to believe, incorrectly, that simply carrying so much cash was illegal, he claimed it belonged to a friend. The money was seized under suspicion that it—not Parhamovich—had been involved in a drug crime. Since Parhamovich had denied the money was his, he could not claim it. The fictional friend, of course, also could not claim the money. As a result, the State of Wyoming maintained that the money was abandoned. The State maintained this, in part, because of Parhamovich’s statement that the money was not his. This statement is hearsay, but would be admissible, at least prima facie, as an opposing party statement. At first glance, the Crawford doctrine might seem to supersede the opposing party statement exclusion. This doctrine prohibits the admission of testimonial hearsay against criminal defendants. However, the Crawford doctrine applies only in criminal cases, and civil asset forfeiture proceedings are not considered criminal. This Note argues that the historical sources cited in Crawford and later cases suggest that the concerns regarding testimonial hearsay also apply in certain civil contexts, and that Crawford protections should be extended to citizens, like Phil Parhamovich, facing asset forfeiture. Civil asset forfeiture is a prime candidate: it shares important characteristics of criminal proceedings and imposes comparable penalties. Even if the Sixth Amendment is inapplicable in such proceedings, the logic of Crawford suggests that, as a policy matter, confrontation should be available in civil asset forfeiture proceedings. This could be done through legislation or through amendment of the Federal Rules of Evidence (FREs).
Keywords: Crawford v. Washington 541 US 36; Crawford doctrine; Forfeiture; Testimonial hearsay; Civil asset forfeiture; Confrontation; Sixth amendment